2005
DOI: 10.1111/j.1600-051x.2005.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological effect of scaling and root planing in smoker and non‐smoker chronic and aggressive periodontitis patients

Abstract: SRP was effective in reducing clinical parameters in both groups. The inferior improvement in PD following therapy for smokers may reflect the systemic effects of smoking on the host response and the healing process. The lesser reduction in microflora and greater post-therapy prevalence of organisms may reflect the deeper pockets seen in smokers and poorer clearance of the organisms. These detrimental consequences for smokers appear consistent in both aggressive and CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
116
2
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(142 citation statements)
references
References 47 publications
15
116
2
9
Order By: Relevance
“…Some authors showed that, although S may exhibit a worse periodontal clinical condition, their response to periodontal therapy is somewhat similar to that obtained in NS. 4,19 Finally, considering the interdependence between tooth sites, teeth and patients, 20 a multilevel analysis was performed using all six tooth sites. In sequence, the analysis took into consideration the approximal and free surfaces as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors showed that, although S may exhibit a worse periodontal clinical condition, their response to periodontal therapy is somewhat similar to that obtained in NS. 4,19 Finally, considering the interdependence between tooth sites, teeth and patients, 20 a multilevel analysis was performed using all six tooth sites. In sequence, the analysis took into consideration the approximal and free surfaces as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…13,35 In the current study, the reduction in the levels of periodontopathogens (A. actinomycetemcomitans, P. gingivalis, and T. forsythia) in both groups (SM and NS) was 100% after 6 months of therapy. A significant reduction of T. forsythia and A. actinomycetemcomitans levels in both SM and NS, absence of P. gingivalis among NS, and very low detection of P. gingivalis among SM (less than 10%) were observed after 6 months of periodontal treatment in a study conducted by Aptzidou et al 14 The same magnitude of microbiological response was observed for P. gingivalis and T. forsythia 6 months after periodontal treatment in SM and NS by Renvert et al 35 However, these authors observed that A. actinomycetemcomitans increased in SM, demonstrating that this pathogen is more difficult to be eradicated among tobacco users.…”
Section: Discussionmentioning
confidence: 98%
“…2 It remains unclear whether there are differences in the subgingival biofilm composition between SM and NS. Some studies have shown no differences in the prevalence of periodontal pathogens 13,14,15 while other studies have demonstrated higher levels of periodontal pathogens belonging to the red and orange complexes 10,11,12 in SM compared to NS. The present study assessed the prevalence of A. actinomycetemcomitans, P. gingivalis, and T. forsythia at baseline and at 3 and 6 months of treatment and found that only A. actinomycetemcomitans was statistically higher at baseline in SM compared to NS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klinisch gezien zijn er weinig significante verschillen tussen rokers en niet rokers zijn voor wat betreft het resultaat na initiële behandeling (Preber & Bergström, 1985;. Bij patiënten met een ernstige gegeneraliseerde EOP werd wel gevonden dat rokers minder verbeteren na initiële behandeling dan niet rokers (Darby et al, 2005). De schaarse langetermijnstudies tonen aan dat rokers echter meer kans hebben op verder botverlies één jaar na de behandeling dan nietrokers (Meinberg et al, 2001).…”
Section: Roken En Behandeling Van Parodontitis Initiële Behandelingunclassified